Prevalence of gastrointestinal parasites in captive mammals at Khon Kaen Zoo, Thailand - Sangpeng, Jirawat; Eamudomkarn, Chatanun; Hongsrichan, Nuttanan; Artchayasawat, Atchara; Chaisongkram, Chavin; Ponsrila, Kanda; Kimkamkaew, Siriwan; Laoprom, Nonglak; Boonmars, Thidarut; Sithithaworn, Paiboon; Pitaksakulrat, Opal (Veterinary World, 2023)
Background and Aim: Captive animals are susceptible to parasitic diseases due to the stress and confinement they experience. In addition, they can serve as reservoirs of zoonotic parasites that have the potential to infect humans. To investigate this possibility, we estimated the prevalence of gastrointestinal (GI) parasites in captive mammals at Khon Kaen Zoo, Thailand. Materials and Methods: One hundred and forty-seven individual mammals (37 primates, 43 carnivores, 62 herbivores, and 5 rodents) were examined for parasitic infections by fecal examination daily for 3 consecutive days using the formalin-ethyl acetate concentration technique (FECT) and the agar plate culture method. Results: According to FECT, the overall prevalence of GI parasites was 62.6% (92/147). Within animal groups, the numbers were as follows: 67.6% (25/37) in primates, 23.3% (10/43) in carnivores, 85.5% (53/62) in herbivores, and 80.0% (4/5) in rodents. Using the agar plate culture method, 21.43% (27/126) were positive for Strongyloides spp. and hookworm infections. The GI parasites identified belonged to three categories: protozoa (including Entamoeba histolytica species complex, Entamoeba coli, Giardia spp., coccidia, and ciliated protozoa), trematodes (minute intestinal flukes and rumen flukes), and nematodes (strongyle/hookworm, Strongyloides spp., Ascarididae, and Trichuris spp.). Conclusion: The findings of this study indicate the prevalence of several GI parasites in zoo animals with the potential for transmission to humans, given the animals’ close proximity to both visitors and animal caretakers. Keywords: captive mammals, gastrointestinal parasites, zoo, zoonotic parasites.